2021
DOI: 10.4103/jfmpc.jfmpc_2345_20
|View full text |Cite
|
Sign up to set email alerts
|

A study on contraceptive prevalence rate and factors influencing it in a rural area of Coimbatore, South India

Abstract: Introduction: India is the first country to implement National Family Program in 1952. Acceptance of contraceptive methods is influenced by various factors at the individual, family, and community level with their roots in the socioeconomic and cultural milieu of Indian society. This study was carried to find the contraceptive prevalence rate among eligible couples as well as to find the factors influencing it in a rural area of Coimbatore. Methodology: The study was ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 10 publications
0
0
0
Order By: Relevance
“…The study found that unemployed women (19;31.7%) used contraceptives more than employed women (45;30.2%). This contrasts with some previous research that has found that employed women are more likely to use contraception, possibly due to their higher awareness of its benefits and socioeconomic status [12] .…”
Section: Discussioncontrasting
confidence: 99%
“…The study found that unemployed women (19;31.7%) used contraceptives more than employed women (45;30.2%). This contrasts with some previous research that has found that employed women are more likely to use contraception, possibly due to their higher awareness of its benefits and socioeconomic status [12] .…”
Section: Discussioncontrasting
confidence: 99%
“…Female sterilization was the most preferred choice after family completion by the participants (36.50%) which was lower compared to Osborn A J et al study (86.1%). 1 In our study, the major reason for non use of contraceptive method was opposition from husband (36.75%) and fear of side effects (18%) where as in Nair V R et al study in Tamil Nadu the couples did not feel the need to use any contraceptive methods (28.6%). 14 In a study done by Bandhi G et al and Prateek S S et al there was a significant association between the age groups of study participants and…”
Section: Discussionmentioning
confidence: 45%
“…Within few years, this under 15 years age group will enter the reproductive age which will further cause increase in the population growth. 1,2 The result of this exponential growth leads to economical crises and further stress on the limited resources. India's landmass is only 2.4% of the total landmass of the world but 17% of the world population lives here.…”
Section: Introductionmentioning
confidence: 99%
“…Our study reported a higher use of temporary methods (75%) as compared to permanent methods. Contrary results were found in studies by Patel et al, Osborn et al, Shree et al and Nanda et al 10,[21][22][23] The reason for the higher use of temporary methods could be the higher percentage of participants in the younger age group who prefer spacing to limit.…”
Section: Resultsmentioning
confidence: 67%